Productivity of Boran cattle maintained with chemoprophylaxis under high tsetse challenge at Mkwaja ranch in Tanzania. 1. Ranch organization and animal health management - Jibbo, J.M.C.; Trail, J.C.M.; Sones, Keith R.; Durkin, J.W.; Light, D.E.; Murray, M. (1985)
Mkwaja Ranch is located on the coast of Tanzania in Pangani District about 100 km south of Tanga. The ranch covers an area of 47,250 hectares of coastal forest-savanna mosaic vegetation. The area is heavily infested with three species of tsetse, Glossina morsitans morsitans, G. pallidipes and G. brevipalpis, the challenge being such that cattle cannot survive unless treated with trypanocidal drugs. Mkwaja ranch was established by Amboni Limited, in 1954. Although known to be infested with tsetse, the decision to set up the ranch was made due to the availability of the prophylactic drug Antrycide prosalt. The original objective was to rely on trypanocidal drugs in the short term with the long term aim of controlling the tsetse. However, by 1964, efforts to control tsetse were abandoned (apart from the sterile male experiment in the 1970s) and a chemo- prophylactic regime based on the use of isometamedium chloride (Samorin) was adopted. Over the last 10 years, the ranch has supported some 12,000 head of Zebu cattle progressively upgraded since 1958 by the importation of Boran bulls and semen from Kenya. From 1973 to 1980, breeding cows, heifers, bulls and steers were maintained under Samorin prophylaxis at 0.5 mg/kg on a herd basis. One month after the last pro-phylaxis 30 to 40 animals per herd (herds average 225-300) were examined at one to two weeks intervals for trypanosome infection. When approximately 20% of the sample was positive, the entire herd was treated. In addition, all sick looking animals were examined for trypanosomes and if positive before the next Samorin treatment of the herd was due, these animals were treated with Berenil at 3.5 mg/kg. All pre-weaning calves were treated at monthly intervals with Berenil. In June 1980, the strategy was changed so that beginning 2 months after the last prophylaxis, as soon as the first positive cases were detected; the entire herd was treated with Berenil and one week later with Samorin at 1 mg/kg. However, in late 1981 and 1982, only Samorin was used as Berenil was not available. The strategic use of trypanocides reduced death from trypanosomiasis to an absolute minimum, 1% of all calves and 3% of adults necropsied, in an area where cattle if left untreated rapidly succumb to trypanosomiasis. In addition to the successful trypano- cidal drug strategy , the proper management of acaricides, anthelmintics, and bacterial and viral vaccines kept major infectious diseases on Mkwaja under control and annual mortality to less than 10%; predators were responsible for 30% of this total.